Influence of soot aging on soot production for laminar propane diffusion flames. (15th December 2017) - Soussi, J.P.; Demarco, R.; Consalvi, J.L.; Liu, F.; Fuentes, A.
Abstract: A numerical analysis was conducted to investigate the effect of varying the Oxygen Index (OI) of the oxidizer stream between 21 and 35% on soot production and thermal radiation emitted by laminar axisymmetric propane diffusion flames at atmospheric pressure. The extended enthalpy defect flamelet model, an acetylene/benzene-based two-equation semi-empirical soot production model, and the Full-Spectrum correlated-k radiative property model were used in the numerical simulations. The focus of this study is to demonstrate that it is important to account for the soot aging effect to correctly predict how increasing OI affects the predicted soot production. Three soot surface growth rate models were considered. The first model neglects the soot aging effect and assumes the soot surface growth rate is linearly dependent on soot surface area. The second and third models account for the soot aging effect by assuming the soot surface growth rate is proportional to the square-root of soot surface area and assuming a particle size-dependent sublinear soot surface area, respectively. The predicted flame height, soot volume fraction, radially integrated soot volume fraction and radiant fraction were compared to available experimental data. The first soot model predicted a much higher soot loading increase with increasing OI than observed experimentally. The second and third soot models improve considerably the predicted general behavior of soot loading increase with OI. Soot and combustion gases make comparable contribution to flame radiation under the conditions studied. When the soot aging effect is properly taken into account, the relatively efficient numerical code assessed in this study becomes a suitable tool for predicting soot production and thermal radiation in laminar propane diffusion flames at different OI conditions. Moreover, increasing OI of the oxidizer stream is a remarkable way to enhance the flame radiation where the correct estimation of soot production is essential to predict the radiant fraction of the flame.